2020
DOI: 10.1083/jcb.202006101
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of membrane NMDA receptors by dynamics and protein interactions

Abstract: Understanding neurotransmitter system crosstalk in the brain is a major challenge in neurobiology. Several intracellular and genomic cascades have been identified in this crosstalk. However, the discovery that neurotransmitter receptors are highly diffusive in the plasma membrane of neurons, where they form heterocomplexes with other proteins, has profoundly changed our view of neurotransmitter signaling. Here, we review new insights into neurotransmitter crosstalk at the plasma membrane. We focus on the membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 178 publications
(231 reference statements)
0
19
0
Order By: Relevance
“…An antibody that recognizes only the NR1 C2 isoform was used in this study. Prior work on NMDAR surface dynamics at the neuronal plasma membrane have shown that NMDAR at the postsynaptic density exhibit confined diffusion with anchoring of receptors but high diffusion with low confinement in the extrasynaptic membrane 57 . These differing NMDAR pools, synaptic vs extrasynaptic, mobile vs immobile, might depend on whether NMDAR contain the NR1 C2' or NR1 C2 subunit.…”
Section: Discussionmentioning
confidence: 99%
“…An antibody that recognizes only the NR1 C2 isoform was used in this study. Prior work on NMDAR surface dynamics at the neuronal plasma membrane have shown that NMDAR at the postsynaptic density exhibit confined diffusion with anchoring of receptors but high diffusion with low confinement in the extrasynaptic membrane 57 . These differing NMDAR pools, synaptic vs extrasynaptic, mobile vs immobile, might depend on whether NMDAR contain the NR1 C2' or NR1 C2 subunit.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, proteins have been utilized as biomarkers for tissues, cell types, developmental stages, disease states, and as potential targets for drug discovery and interventional approaches. Then, the identification of biomarkers of parasitic infections by differential protein profiling of specific hosts or parasitic molecules is a promising area [48][49][50][51][52] . In this context, membrane proteins have been proposed as interesting candidates in different organisms.…”
Section: Discussionmentioning
confidence: 99%
“… 2 However, NMDAR antagonists all unfortunately failed to show protective effects in human patients, which was due to the limited understanding of the pathological regulation of NMDAR during ischemic stroke. 3 , 4 Based on their location, NMDARs are divided into synaptic NMDARs (sNMDARs) and extrasynaptic NMDARs (esNMDARs). 5 During ischemic stroke, sNMDARs promote neuron survival, while esNMDARs cause neuronal death.…”
Section: Introductionmentioning
confidence: 99%